A Theoretical approach to the equity vs. efficiency argument for income taxes - Al-Majid, Ahmed Waris (BRAC University, 2014)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Science in Applied Economics, 2013.